The crisis of Qatari-Gulf relations and its repercussions on the Qatar Stock Exchange - Falah Hassan Ahmed (The Scientific Journal of Cihan University– Sulaimaniya, 2020)
This research aims to study the impact of the Qatari - Gulf relations crisis on the stock price indices and their impact on the percentage of foreign trades on the Qatar Stock Exchange. The research community was represented on the Qatar Stock Exchange. The research was applied to all sectors listed on the Qatar Stock Exchange as a sample of research. On a monthly basis, it ran from May 2015 to June 2019. The research was based on the statistical analysis method to test the research hypotheses, as the program (SPSS - Version 24) was used in data analysis. The research concluded to a number of conclusions, the most important one is that there is negative impact of the crisis of Qatari-Gulf relations in the stock price indices in the Qatar Stock Exchange. It also concluded that the ratios of foreign trades were not affected by that crisis. To take the necessary measures that would limit its negative effects on the market and the listed companies, such as allow increasing the percentage of foreign investors owning shares of listed companies.